مدى تحمل الزوج لمسؤوليته في الإنفاق على زوجته العاملة: دراسة ميدانية في مدينة سطيف بالجزائر: Does The Husband Pay Maintenance for The Working Wife: A Field Study in The City of Setif, Algeria - Guellou, Nourah; Azahari, Raihanah (Jurnal Syariah, 2012)
This article attempts to identify the rights of maintenance for working wives. This study was conducted on 270 working wives in the City of Setif. Empirical data were collected through questionnaires to identify certain issues: 1- The factors that cause them to work; 2 - Does the husband pay the maintenance for the working wife? And 3 - What are the problems faced by the working wife for their maintenance? The data were analysed quantitatively using SPSS based on the frequency and percentage. This study found that 97% of wives go out to work because they have the expertise or qualifications to qualify them for employment. FurthermoreØŒ 65.6% wives said their husbands would ask for money from them if the money spent is allocated for domestic needs and the wife would usually help their husbands by giving money at the end of the month. The study also found that most of the husbands and wives have joint savings accounts. The most common problems faced by working wives (40.5%) is that their husbands would ask them to pay the bills when there is an increaseØŒ and usually their husbands will inspect all the goods purchased by them and consider they are a waste. Most working wives do not get monthly maintenance because they are considered to already have their own income.